O uso de tecnologias da informação móveis e sem fio no monitoramento e controle de projetos - Comin, Everton Roberto (Universidade do Vale do Rio dos Sinos, 2013)
ABSTRACT The development of projects by organizations is a widely used practice to get different results. However, dissatisfaction with the results obtained is not an exception. Among the factors influencing project performance is the efficient and effective implementation of processes related to monitoring and controlling the project. The use of mobile technologies can contribute to the execution of processes in which workers have mobility characteristics. The objective of this study is to investigate ways that the use of mobile technologies in project monitoring and controlling processes affects project performance. The methodology used to achieve this objective was based on the realization of an exploratory stage in which we interviewed project managers to better understand the phenomenon. A conceptual model that demonstrates the relationship between the degree of use of mobile technologies in the project monitoring and controlling processes and projects performance was proposed. It was based on respondents' perceptions and theoretical review of project management and mobile technologies. A survey was conducted with project managers for empirical verification of the model. At the end of the survey sample consisted of 223 respondents. We used the statistical technique of Partial Least Squares (PLS). During validation of the model it was necessary to remove the construct dependence on location. The analysis of the results showed that the relation between the critical time and the use of mobile technologies is not of statistical significance in the context of research. Moreover, the mobility construct has a statistically significant relationship with the use of mobile technologies. Likewise, the use of mobile technologies in project monitoring and controlling processes has statistically significant relationship with project performance. The results indicate a positive relationship between the use of TIMS in project monitoring and controlling processes and project performance, particularly with respect to time. We highlighted the limitations of the survey method of measuring the mobility of the project manager and the verification of the use of mobile technologies just in project monitoring and control processes. We suggest for future research the improvement of the method of measuring the mobility of project managers and the inclusion of the analysis of the use of mobile technologies in other processes related to project management that may affect project performance.
Keywords: Tecnologias da Informação Móveis e Sem fio; Processos de Monitoramento e Controle do Projeto; Mobile Technologies; Project Monitoring and Controlling Process; Project performance; Desempenho dos projetos; ACCNPQ::Ciências Sociais Aplicadas::Administração